OP0107 Pain still remains a high unmet need among psoriatic arthritis patients receiving existing biologic treatment: results from a multi national real-world survey. (15th June 2017) - Conaghan, PG; Strand, V; Alten, R; Sullivan, E; Blackburn, S; Huneault, L; Tian, H; Gandhi, K; Jugl, S
Abstract : Background: Many patients diagnosed with Psoriatic Arthritis (PsA) experience pain which can persist during treatment and may impair health related quality of life (HRQOL) and the ability to work. Objectives: To assess self-reported pain in patients with PsA receiving biologic therapy, and evaluate the association of increasing severity of pain with HRQOL and employment status. Methods: Cross-sectional survey data from Rheumatologists and Dermatologists (specialists) treating PsA and their patients in 13 countries spanning the Americas, Asia Pacific, EU, Turkey and the Middle East were analyzed. A geographically diverse sample of specialists in each country completed a detailed form for consecutive consulting PsA patients recording information such as demographics, clinical state and treatment details. Patients voluntarily completed questionnaires providing demographics, self-reported intake of non-prescription pain medication, work status, HRQoL (EQ-5D, SF-36), impairment in physical function (HAQ-DI), and impairment in work productivity and activity (WPAI). Patient reported pain was stratified using tertiles of the SF-36 "Bodily Pain" (BP) subdomain. Results: Results are presented from 782 patients with PsA receiving traditional biologic treatment (mainly anti-TNF) for ≥3 months who completed SF-36 questionnaires. SF-36 BP domain tertiles were: no/mild pain: BP: >75 to 100: 33.1%; moderate: BP: >52 to ≤75: 30.1%; and severe: BP: 0 to ≤52: 36.8%. A strong positive linear relationship between BP tertiles and EQ-5D pain was observed (correlation coefficient: 0.6678). More severe pain was associated with increased use of prescription NSAIDS (p=0.0026) and opioids (p=0.0065), as well as non-prescription pain medication (p<0.0001). The level of HRQOL impairment among PsA patients increased as pain increased: SF-36 domains (excluding BP) were lower, all differences were clinically 1 and statistically significant (all p<0.0001); EQ-5D domains (excluding pain/discomfort) were also lower (p<0.0001). More severe pain was associated with greater disability (higher HAQ-DI scores), and greater activity impairment, overall work impairment, work time missed and impairment while working due to PsA (all p<0.0001). Among patients of working age (≤65), the likelihood of unemployment or retirement due to PsA was higher among patients reporting severe pain: Mild (n=21): 19.0%, Mod (n=30): 10.0%, Severe (n=36): 58.3%; p<0.0001. Conclusions: This analysis of real world patient reported data suggests that pain is common among PsA patients receiving biologic therapy. Increasing severity of pain is associated with more impaired HRQOL, physical functioning, engagement in activities and work productivity. These results suggest there is a need for treatments that provide fast and sustained improvement in pain to reduce the impact pain has on patients' daily life as well as societal costs. References: Ware J, et al. User's Manual for the SF-36v2® Health Survey. Lincoln (RI): QualityMetric Incorporated; 2007:125–133. Strand et al. Ann Rheum Dis. 2009 Dec; 68(12): 1800–1804. Disclosure of Interest: P. Conaghan Consultant for: Abbvie, Eli Lilly, Novartis, Pfizer, Speakers bureau: Abbvie, BMS, Roche, V. Strand Consultant for: AbbVie, Amgen, BMS, Celgene, Celltrion, CORRONA, Genentech/Roche, GSK, Janssen, Lilly, Merck, Novartis, Pfizer, Regeneron, Samsung, Sanofi, UCB, R. Alten Grant/research support from: Novartis Pharma AG, Speakers bureau: Novartis Pharma AG, E. Sullivan: None declared, S. Blackburn: None declared, L. Huneault Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG, H. Tian Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation, K. Gandhi Shareholder of: Novartis Pharmaceuticals Corporation, Employee of: Novartis Pharmaceuticals Corporation, S. Jugl Shareholder of: Novartis Pharma AG, Employee of: Novartis Pharma AG